Testing of a full-scale flat slab building for gravity and lateral loads. (15th September 2021) - Coronelli, Dario; Lamperti Tornaghi, Marco; Martinelli, Luca; Molina, Francisco-Javier; Muttoni, Aurelio; Pascu, Ion Radu; Pegon, Pierre; Peroni, Marco; Ramos, António Pinho; Tsionis, Georgios; Netti, Teresa
Highlights: Earthquake and cyclic tests on a full-scale RC flat-slab building structure. Flexural and punching behaviour of slabs with and without transverse reinforcement. Punching shear strengthening of RC flat slabs using post-installed bolts. Abstract: Full-scale testing of a two-storey flat slab structure is reported, undertaken in the SlabSTRESS research project; the construction and testing were planned and carried out at the ELSA laboratory of the European Commission's Joint Research Centre. The dimensions are three bays by two, spans 4.5 and 5 m, slab thickness 0.2 m, interstorey height 3.2 m. Two different longitudinal reinforcement details were considered; welded studs shear reinforcement was provided only in the second floor slab. The testing program included seismic tests for service and ultimate actions, using the pseudodynamic technique with virtual walls. To this aim a building structure was designed with primary walls and the flat slab frame as secondary element. Cyclic loading tests followed up to ultimate drift capacity of the structure. The sequence of tests included strengthening of a set of damaged connections using bolted bars in holes drilled through the slab, followed by cyclic testing to failure. The instrumentation was provided for the global response and the connections with local rotations in the columns and slab; cracking around the columns was measured with through-crack sensors; a measurement system for internal forces and moments was included within the columns. The results show the response with deformations and damage for the different loading conditions up to failure. The results obtained on a full-scale structure extend and confirm the knowledge in the literature, mainly based on isolated connections and/or small-scale samples.